Synthesis and characterization of membranes obtained by graft copolymerization of 2-hydroxyethyl methacrylate and acrylic acid onto chitosan - Santos, K. S. C. R. dos (2006)
Chitosan based membranes to be applied on wound healing as topical drug delivery systems were developed by graft copolymerization of acrylic acid (AA) and 2-hydroxyethyl methacrylate (HEMA) onto chitosan using cerium ammonium nitrate as chemical initiator. Evidence for graft copolymerization of the vinyl monomers onto chitosan was obtained by FTIR and DMTA. Swelling degree, cytotoxicity, thrombogenicity and haemolytic activity of these membranes were evaluated. Chitosan-graft-AA-graft-HEMA showed to be the best matrix for drug delivery systems than chitosan-graft-AA because it retains good swelling properties, but the content in HEMA has improved cytocompatibility, hemocompatibility and thrombogenic character.